Global religions and international relations: a diplomatic perspective - Ferrara, Pasquale; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2014)
With a religious re-emergence in international relations, this book provides an introduction to the role religions play within the global political arena. Culled from theoretical, practical, and real-world experiences, Ferrara explains the role religion now plays in global affairs on diplomatic and political levels.
Keywords: Religion; Religion and sociology; Political science; Political theory; International relations; Political philosophy; Religious Studies; Religion and Society; Political Theory; Political Philosophy; Social Aspects of Religion; International Relations